Comparison of the Effect of Honey, Olive, Propolis Combined Vaginal Cream With OCP in the Treatment of Functional Ovarian Cysts in Women of Reproductive Age Referring to Health Centers, Hamadan, Iran 2020-2021 - Shayan, Arezoo; Parsapour, Hamideh; Hosseinpoor, Mehrnoosh; Masoumi, Seyedeh Z.; Kazemi, Farideh; Moradkhani, Shirin; Hossein Oliaei, Seyed Mohammad; Assareh, Zeinab; Rashidi, Mohammad Kazem (Current Women's Health Reviews, 2024)
Background: The prevalence of functional ovarian cysts in women is high, and choosing an appropriate, and uncomplicated treatment is necessary. Objective: Compare the effectiveness of honey, olive, and propolis combined vaginal cream with OCP in the treatment of functional ovarian cysts in women of reproductive age in Iran. Methods: This randomized clinical trial study was performed on 40 women of reproductive age referred to Hamadan health centers in 2020. Patients were randomized into two groups, A and B. Group A received oral contraception pills for two consecutive cycles from the seventh day of the menstrual cycle tablets for 21 days after the end of menstruation until the beginning of the next menstruation. Group B received honey, olive, propolis combined vaginal cream. In both groups, the treatment continued for two consecutive cycles. Data was collected through a checklist that included clinical symptoms and ultrasound results. The results were analyzed by Stata-13 and the significance level cut-off was considered less than 0.05. Results: Intra-group comparisons showed that there was a statistically significant (P < 0.05) decrease in cyst size after the intervention in both groups. Intergroup differences were not statistically significant (P #131; 0.05). Conclusion: Honey, olive, propolis combined vaginal cream (Nika) can be effective like oral contraceptive pills in reducing the size of ovarian cysts. It can be recommended for the treatment of functional ovarian cysts.
Keywords: Honey